Implementasi Iot dalam Simulasi Pendeteksi Objek Orang yang Masuk Dalam Suatu Ruangan - Muhammad Ricki Ghozali; Ade Putra (CV MEDAN TEKNO SOLUSI, 2025)
This research discusses the Implementation of IoT in the Simulation of Object Detectors of People Entering a Room. Smart people detector calculation system is a technological tool that functions to calculate objects that enter a room so that users can find out information about the number of visitors. The way this tool works is when visitors pass through the sensor that has been installed on the door of the room, the tool will send a signal to the ESP8266 Module to send the information to the LCD to display the information. Smart people detector calculation system is one of the innovation products from REO which is under the auspices of the Directorate of Innovation and Business Incubator (DIIB).